Structured Interventions to Optimize Polypharmacy in Psychiatric Treatment and Nursing Homes: A Systematic Review. Issue 2 (March 2022) - Stötzner, Philip; Ferrebus Abate, Rodolfo Enrique; Henssler, Jonathan; Seethaler, Magdalena; Just, Sandra Anna; Brandl, Eva Janina
Abstract: Background: Polypharmacy is a common clinical issue. It increases in prevalence with older age and comorbidities of patients and has been recognized as a major cause for treatment complications. In psychiatry, polypharmacy is also commonly seen in younger patients and can lead to reduced treatment satisfaction and incompliance. A variety of structured polypharmacy interventions have been investigated. This systematic review provides a comprehensive overview of the field and identifies research gaps. Methods: We conducted a systematic review on structured interventions aimed at optimizing polypharmacy of psychotropic and somatic medication in psychiatric inpatient and outpatient settings as well as nursing homes. A search protocol was registered with PROSPERO (CRD42020187304). Data were synthesized narratively. Results: Fifty-eight studies with a total of 30, 554 participants met the inclusion criteria. Interventions were most commonly guided by self-developed or national guidelines, drug assessment scores, and lists of potentially inappropriate medications. Tools to identify underprescribing were less commonly used. Most frequently reported outcomes were quantitative drug-related measures; clinical outcomes such as falls, hospital admission, cognitive status, and neuropsychiatric symptom severity were reported less commonly. Reduction of polypharmacy and improvement of medication appropriateness were shown by most studies. Conclusions: Improvement of drug-related outcomes can be achieved by interventions such as individualized medication review and educational approaches in psychiatric settings and nursing homes. Changes in clinical outcomes, however, are often nonsubstantial and generally underreported. Patient selection and intervention procedures are highly heterogeneous. Future investigations should establish standards in intervention procedures, identify and assess patient-relevant outcome measures, and consider long-term follow-up assessments. Abstract : Supplemental digital content is available in the text.